Emotion regulation and social cognition as functional targets of mechanism-based psychotherapy in major depression with comorbid personality pathology - Schnell, Knut; Herpertz, Sabine (Journal of personality disorders, 2018)
This article characterizes functional systems as targets of integrated modular psychotherapy for episodes of major depression (MD) with a comorbid condition of borderline personality disorder (BPD) or chronic depression (CD). Both types of comorbidities to MD are conceptualized as a trait-like concept dominated by impairments in interpersonal functioning. Despite differences in psychopathology, existing data show significant similarities in impairments of emotion regulation and social cognition in BPD and CD, thought to reflect common disease mechanisms linked to early-life adversity. The preexistence of BPD and CD and related functional impairments inhibits the remission of episodic MD and calls for mechanism-based interventions that complement existing treatments of MD by targeting these dysfunctions. Contemporary methods of psychotherapy already provide interventions to address such complicated states of comorbidity by specifically improving dysfunctions of emotion regulation and social cognition. We suggest a layout of modular interventions that can address identified dysfunctions in comorbid MD.
Gesehen am 08.04.2020